Ultrasound-assisted sorption of Pb(ii) on multi-walled carbon nanotube in presence of natural organic matter: an insight into main and interaction effects using modelling approaches of RSM and BRT. Issue 28 (24th May 2019) - Foroughi, Maryam; Zolghadr Nasab, Hassan; Shokoohi, Reza; Ahmadi Azqhandi, Mohammad Hossein; Nadali, Azam; Mazaheri, Ashraf
Abstract : The proposed mechanism for effect of HA on Pb(ii ) removal using MWCNTs. Abstract : In real-scale applications, where NPs are injected into the aqueous environment for remediation, they may interact with natural organic matter (NOM). This interaction can alter nanoparticles' (NPs) physicochemical properties, sorption behavior, and even ecological effects. This study aimed to investigate sorption of Pb(ii ) onto multi-walled carbon nanotube (MWCNT) in presence of NOM. The predominant behavior of the process was examined comparatively using response surface methodology (RSM) and boosted regression tree (BRT)-based models. The influence of four main effective parameters, namely Pb(ii ) and humic acid (HA) concentrations (mg L −1 ), pH, and time (min) on Pb removal (%) was evaluated by contributing factor importance rankings (BRT) and analysis of variance (RSM). The applicability of the BRT and RSM models for description of the predominant behavior in the design space was checked and compared using statistics of absolute average deviation (AAD), mean absolute error (MAE), root mean square error (RMSE), and multiple correlation coefficient ( R 2 ). The results showed that although both approaches exhibited good performance, the BRT model was more precise, indicating that it could be a powerful method for the modeling of NOM-presence studies. Importance rankings of BRT displayed that the effectiveness order of the studied parameters is pH > time > Pb(ii ) concentration > HA concentration. Although HA concentration showed the least effect in comparison with three other studied parameters theoretically, the experimental results revealed that Pb(ii ) removal is enhanced in presence of HA (73% vs. 81.77%), which was confirmed by SEM/EDX analyses. Hence, maximum removal ( R % = 81.77) was attained at an initial Pb(ii ) concentration of 9.91 mg L −1, HA concentration of 0.3 mg L −1, pH of 4.9, and time of 55.2 min.